2020
DOI: 10.1080/2090598x.2020.1739382
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of percutaneous renal cryoablation with conscious sedation

Abstract: Objective: To investigate complications and treatment failure rates of percutaneous renal cryoablation (PRC) for small renal masses under local anaesthesia and conscious sedation (LACS), to assess the safety and effectiveness of this approach, as PRC is typically performed under general anaesthesia (GA). Patients and methods: We retrospectively reviewed PRC under LACS from 2003 to 2017. We analysed perioperative parameters between patients who successfully underwent PRC under LACS and patients with post-proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While admittedly, general anesthesia reduces intraoperative patient awareness and recall and offers pain control for prolonged periods of time, thereby allowing for more complex interventions [14], our approach was less invasive, allowing a more sparing use of material and personnel. A number of studies showed that cryoablation under local anesthesia and conscious sedation was as safe and effective as cryoablation under general anesthesia [11][12][13]. In center 1 anesthesiologists considered unfit for treatment with local anesthesia only uncooperative patients or patients who were possibly unable to keep prone position for the entire length of cryoablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While admittedly, general anesthesia reduces intraoperative patient awareness and recall and offers pain control for prolonged periods of time, thereby allowing for more complex interventions [14], our approach was less invasive, allowing a more sparing use of material and personnel. A number of studies showed that cryoablation under local anesthesia and conscious sedation was as safe and effective as cryoablation under general anesthesia [11][12][13]. In center 1 anesthesiologists considered unfit for treatment with local anesthesia only uncooperative patients or patients who were possibly unable to keep prone position for the entire length of cryoablation.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term efficacy results of RCC thermal ablation start being collected and 5-year outcomes of large series treated with cryoablation in single center teaching hospitals, often under general anesthesia, are available [8][9][10]. Cryoablation with local anesthesia and conscious sedation was reported as an alternative modality [11][12][13] and shortened perioperative time and hospital stay [12]. To our knowledge cryoablation under local anesthesia only was not reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Clavien-Dindo complications grade 3 to 5 have never occurred. The distribution of adverse events in this study is truly interesting since, in front of a meaningful higher rate of complications, there were no serious events requiring medical intervention while most of the authors, on the contrary, report some complications of grade 3 or even more in their series [10,15,18,21,35,36]. Some authors have chosen not to report complications below grade 3, evidently considering them not significant [7,29].…”
Section: Discussionmentioning
confidence: 67%